Communication Strategies Used in Bahasa Inggris Textbook for Grade Twelfth of Senior High School - Andrian Nuriza Johan (Scripta : English Department Journal, 2019)
This article is based on a study which aims at the finding out components ofcommmunicaton stratedies and sufficiency of strategic competence in Bahasa Inggristextbook. The data analyzed are the models of speaking text taken from Bahasa Inggristextbook. There are 5 texts in the textbook. The finding of the study reveals there is nocommunication strategies used in the textbook.